The Effect of Lucky Day! If You Lucky Method on Islamic Religious Education Learning Outcomes - Faila Sufah (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
This research is motivated by the learning outcomes of Islamic religious education students who are still not optimal and methods that are still conventional. The purpose of this study was to determine the effect of lucky day! if you lucky method on learning outcomes of Islamic religious education in fourth-grade students of State Elementary School 01 Belinyu. The research method used a quantitative approach. The type of research is true experimental with a posttest-only control design. Data collection techniques used objective tests in the form of written tests of multiple choice questions. The study population was all students of Elementary School 01 Belinyu, which amounted to 299 students. The research sample was 52 fourth-grade students of State Elementary School 01 Belinyu who were selected using purposive sampling, namely the deliberate selection of samples consisting of 26 experimental class students and 26 control class students. The research instrument was a test. Data analysis used an independent sample t-test. The results showed that there was an effect of lucky day! if you lucky method on the learning outcomes of Islamic religious education fourth-grade students of State Elementary School 01 Belinyu as evidenced by the hypothesis test p-value of .000 < 0.05. Therefore, it can be concluded that the lucky day! if you lucky method has a significant role in improving the learning outcomes of Islamic religious education.